Scientific Role of ‘Āisyah Binti Abu Bakr: A Critical Study on Muhammad Sa’id Ramadan Al-Buti in ‘Aisyah Umm al-Mukminin Ayyamuha wa Siratuha al-Kamilah fisafahat - Rochimah (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This article aims to examine the views of Said Ramadan al-Buti in the book of 'A<isyah Umm al-Mukmini>N Ayya>muha> Wa Si>ratuha> al-Ka>milah fi> Safaha>t about the scientific role of 'Aisyah in spreading and developing the religion of Islam after the Prophet. To answer these questions, this article uses qualitative research methods with the type of library research. The main data source in this study is the book of 'A<isyah Umm al-Mukmini>N Ayya>muha> Wa Si>ratuha> al-Ka>milah fi> Safaha>t, while the secondary data source comes from books and articles that discuss the role of Aisha. From the above question, it was found that it was not only men who played an active role in spreading Islam. Women also have a role in developing the religion of Islam. 'Aishah Bint Abu Bakr was one of the women who played a very active role. The 'scientific role' of Aisyah as a remarkable woman is beyond doubt. The Prophet (peace and blessings of Allaah be upon him) used to say that the Prophet (peace and blessings of Allaah be upon him) used to pray. The breadth of knowledge and extraordinary understanding did not make Aisyah proud. 'Aisyah remained polite, adding that Aisyah's charisma became an exemplary woman.